ANALYSIS OF BETEL NUT VALUE CHAIN FOR EXPORT PURPOSES IN AGAM REGENCY - Farid Azel; Ismet Suryadi; Syafri Amir; Suhadi; M.Syaqib Sidqi; Ispinimiartriani (CV. Radja Publika, 2023)
The demand for betel nut from international markets is continuously increasing, but the agricultural supply chain for this product is quite complex and requires special handling, thus affecting the agricultural product's price. Therefore, research on the analysis of betel nut value-added supply chains is crucial to determine the amount of additional value from each stage and actor involved in the supply chain. The research was conducted in Palembayan, Agam, and Padang, West Sumatra from May to August 2022 using qualitative and quantitative descriptive analysis methods with primary data from experts and farmers and secondary data from literature studies and related sources. This study found that betel nut has the potential to be exported to several countries, such as India, Iran, and the United Arab Emirates, but there are several problems hindering the distribution process. The betel nut supply chain involves several parties, ranging from suppliers to exporters, and there is no contractual relationship between them. This study also identifies criteria for betel nut suitable for export, including low water content, uniform color, large size, meeting food safety standards, and high sugar content. The process of exporting betel nut from Indonesia to India involves selection and collection, processing and packaging, transportation, and export. Thus, betel nut cultivation in Agam Regency can be effective, efficient, and sustainable by increasing the value-added at each production stage.